The Innovative Marketing Strategy to Introduce Traditional Woven Fabrics of Kubang as a Minangkabau Cultural Heritage - Sari, Dilla Engla; Putri, Atika Dwi; Syukirman, Alvi; Evanita, Susi; Friyatmi, Friyatmi; Purnomo, Try Wahyu (Gondang: Jurnal Seni dan Budaya, 2023)
Kubang Payakumbuh Weaving is a cottage industry that produces traditional woven fabric using the unique weaving techniques of the Minangkabau culture. The efforts of the Kubang Payakumbuh Weaving UMKM to maintain and modernize the weaving production are aimed at remaining relevant in an increasingly advanced era. They have adopted contemporary technology and designs to enhance the attractiveness of Minangkabau woven products, thus reaching a wider market. The marketing strategy employed by the Kubang Payakumbuh Weaving UMKM to promote their products involves the use of social media and e-commerce platforms to increase the visibility and accessibility of Minangkabau woven products globally.This research reveals the positive impact of innovation and marketing strategies by the Kubang Payakumbuh Weaving UMKM in introducing the cultural heritage of Minangkabau to both local and international communities. Not only do they preserve the weaving tradition, but they also create new economic opportunities for the local community. The research methodology includes observations and interviews with the owners of Kubang Payakumbuh Weaving UMKM as well as their customers. The collected data is qualitatively analyzed to understand the implementation of innovation and its impact on the introduction of Minangkabau cultural heritage. In conclusion, the innovation of the Kubang Payakumbuh Weaving UMKM in introducing the cultural heritage of Minangkabau has brought about positive changes to the traditional weaving industry. Through the use of technology and smart marketing strategies, they have been able to expand their market and introduce the richness of Minangkabau culture to the world.